Retelling the Stories, Rewriting the Bildungsroman: Cecilia Manguerra Brainard's When the Rainbow Goddess Wept - Abao, Frances Jane P. (Humanities Diliman: A Philippine Journal of Humanities; Vol 2 No 1 (2001), 2007)
The traditional Bildungsroman has been criticized for its androcentrism and its upholding of bourgeois values. This paper presents a reading of Cecilia Manguerra Brainard's novel When the Rainbow Goddess Wept as a reworking of the traditional (white European male) Bildungsroman. The novel combines elements of both the female Bildungsroman and the ethnic American Bildungsroman to create a narrative of development that centers on its narrator Yvonne's "becoming Filipina." Intermingling talk stories, Filipino myths and legends, women's personal histories, and women's "alternative" narratives of war, the novel parallels Yvonne's personal development with the development of a collective Filipino "self." Yvonne's ongoing journey towards self-discovery through the recovery of both her personal and racial pasts thus functions as a metaphor for the Filipino nation's own process of rediscovery.